A Study on the Sustainability of Homestays in Kodagu District after the Disaster - August- 2018 - V. , Varsha; S. Sri Ranjini (International Journal of Psychosocial Rehabilitation, 2020)
Kodagu, a district in the state of Karnataka, India, is known as the ’SCOTLAND OF INDIA,’ and it is also called the ’SECOND KASHMIR OF INDIA’ because of its geographical diversity. In the year 2018, very heavy and unprecedented rainfall battered the region into massive destruction, where more than 20 villages were affected, many people lost their lives, and there was also severe damage to their property due to landslides and floods. This has made the region economically and socially weak, where most of the people’s income is through either coffee estates or homestays or both. This study makes an attempt to understand the sustainability of homestays and to study the economic & social downfall. This study includes owners of the homestays, the local community, and tourists.